New Analytical Methodology for Sb(III) Traces Quantification as Emergent Contaminant in Drinks Packaged PET Samples by Solid Surface Fluorescence - Talio, María Carolina (2019)
Emerging contaminants constitute a set of substances that are released into the environment for which regulations are currently not established for their environmental monitoring, being antimony one of them. A new methodology for Sb(III) traces monitoring by solid surface fluorescence is proposed. The metal was complexed with alizarine (Az) as fluorosphore reagent in alcaline medium in presence of the bile salt sodium cholate. To isolate the analyte of matrix constituents, a preconcentration/separation strategy on filter paper was introduced prior to determination step. The solid surface fluorescence was measured λem = 450 nm and λexc = 363 nm using a solid sampler holder. Under optimal conditions, the limits of detection and quantification of proposed methodology were 0.08 and 0.24 μg·L-1, respectively, showing a linear range from 0.24 to 304.4 μg·L-1 with good sensitivity and adequate selectivity. It was applied to the Sb(III) traces determination present in drinking water and beverages samples packaged in polyethylene terephthalate (PET) bottles widely consumed in Argentina. The combination of a preconcentration step on common filter paper and the inherent sensitivity of photoluminescent methods have permitted to achieve sensitivity similar to atomic spectroscopies using a lower price instrument typical in control laboratories. Precision and accuracy were tested with excellent agreement. Results were truenessed by ETAAS with satisfactory concordance.